2014
DOI: 10.5505/tjtes.2014.93876
|View full text |Cite
|
Sign up to set email alerts
|

Intraorbital wooden foreign body: clinical analysis of 32 cases, a 10-year experience

Abstract: BACKGROUND: We aimed to describe herein the clinical features, diagnosis and treatment of intraorbital wooden foreign body injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 17 publications
1
35
1
Order By: Relevance
“…2,3 In a 2014 analysis of 32 cases, CT imaging was definitive in 72% of cases and suggestive in 28% of cases. 4 The detection of wooden foreign bodies is challenging, because wood is typically of low attenuation and can mimic air or fat on the standard CT window settings, although the density can be highly variable. 2,[5][6][7] Prior studies have reported ranges in HU based on the type and state of wood.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In a 2014 analysis of 32 cases, CT imaging was definitive in 72% of cases and suggestive in 28% of cases. 4 The detection of wooden foreign bodies is challenging, because wood is typically of low attenuation and can mimic air or fat on the standard CT window settings, although the density can be highly variable. 2,[5][6][7] Prior studies have reported ranges in HU based on the type and state of wood.…”
Section: Discussionmentioning
confidence: 99%
“…Wooden foreign bodies present low density or even are invisible on CT scan. The quantity and composition of foreign bodies are very difficult to identify, and the CT images of wooden foreign bodies will vary with time, which often leads to misdiagnosis or missed diagnosis 3, 4, 5. Wooden foreign bodies due to the pore on their surface and the characteristics of organic matter, are a great bacterial growth medium, and if not promptly removed, they may lead to infection 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional radiography is the primary imaging modality for detection of FBs; however, superimposition of tissues in the path of X ray beam is the main drawback of 2D imaging (9-11). Non- radiopaque objects cannot be identified by this modality.…”
Section: Introductionmentioning
confidence: 99%